Techno-economic comparison of various process configurations for post-combustion carbon capture using a single-component water-lean solvent - Jiang, Yuan; Mathias, Paul M.; Freeman, Charles J.; Swisher, Joseph A.; Zheng, Richard F.; Whyatt, Greg A.; Heldebrant, David J. (International journal of greenhouse gas control, 2021)
•Developed property models for a novel water-lean solvent based on experimental data.•Designed and simulated seven process configurations for post-combustion carbon capture using the water-lean solvent.•Recommended optima operating conditions for the water-lean solvent.•Conducted techno-economic comparison between seven carbon capture configurations using a water-lean solvent at optimistic, baseline and conservative schemes. Aqueous amines-based absorption is the most mature and scalable technology for post-combustion carbon capture, but subject to high energy and capital investment costs. Water-lean solvents, with associated advanced process configurations, show promise of significantly reducing both energy and capital costs via lower solvent recirculation and lower water condensation and vaporization. Even though advanced process configurations have been intensively studied for aqueous amines, few discussions can be found in the open literature for water-lean solvents. In order to fill the gap, the present study focuses on the process designs towards lower carbon capture cost enabled by water-lean solvents. N-(2-ethoxyethyl)-3-morpholinopropan-1-amine (EEMPA), a single-component water-lean solvent, was selected as an archetypical water-lean solvent. A property package was developed for the H2O−CO2-EEMPA system based on experimental data. Process models were developed in Aspen Plus for 90% CO2 capture in a 550 MW supercritical pulverized coal power plant, with optimal operating conditions determined by sensitivity studies. Techno-economic analyses were performed to compare seven process configurations: simple stripper, two-stage flash, lean vapor compression, inter-heated column, advanced flash stripper, low-pressure steam heater, and advanced heat integration. The results show a two-stage flash configuration, has a carbon capture cost of $47.1/tonne CO2 (in 2011 US dollars), about 19% lower than the industrial benchmark, Cansolv. While considerable capture cost reductions have been proven for aqueous amine using lean vapor compressor and advanced flash stripper, those configurations were shown to have negligible impacts with water-lean solvents due to differences in solvent’s physical properties.